Successful English Learners in Speaking English at SMAN 2 Surabaya: Pembelajar Bahasa Inggris yang Berhasil dalam Berbicara Bahasa Inggris di SMAN 2 Surabaya - Liansari, Vevy (JEES (Journal of English Educators Society), 2016)
It is aimed to investigate the learning strategies used by successful English learners of SMAN 2 Surabaya to assist in converting controlled process into automatic one. Adopting qualitative descriptive analysis, this study consistently describes the phenomena. Notably, it is designed as a case study since the researcher is interested in describing some aspects of second language performance of the subjects as individuals. The researcher used in collecting the data is an interview and supported by the researcher as the observer of the observation conducted in the classroom. The subjects of this study are two successful English learners of eleventh grade senior high. Thus, the data got from the subjects derived from the observation and interview selected, simplified, and organized to draw the conclusion. Based on the results, successful English learners use both direct and indirect strategies in learning to speak English. In applying direct strategy they make use of compensation and cognitive strategy by switching their target language to his mother tongue, using resources for receiving and sending messages in the target language and use mime or gesture. Indirect strategy is applied by making use metacognitive, affective, and social strategy. They also do activities such as paying attention to the language learning tasks, delaying speech production to focus on listening to the target language, cooperating with peers, cooperating with proficient users of target language, seeking practice opportunities, making positive statements, taking risk wisely, and self monitoring, progressive relaxation and has deep breathing.